The system of catalogues in SPSL SB RAS: stages and prospects of development - A. A. Stukalova (Библиосфера, 2014)
Changes in the structure of system of catalogs and card files of SPSTL SB RAS are considered. Characteristics of the main electronic and card catalogs of the library are given.